The role of autobiographical reasoning in the shared experience pathway to identity fusion - Tasuji, T (2019)
Identity fusion – a visceral sense of oneness with the group linked to extreme pro-group action in adults – is thought to result from at least two distinct pathways, namely shared experience and shared biology. The main objective of this thesis was to focus on the shared experience pathway – in which self-defining memories about intensely emotional events are perceived as shared with other group members – in populations largely unexplored in previous fusion literature, namely children, adolescents, and women. Autobiographical reasoning about shared personal experiences – the cornerstone of narrative identity – in conjunction with other post-event processes, were examined across three studies. Study 1 explored the role of autobiographical memory processes in the emergence of identity fusion over the course of development. Findings showed that while identity fusion could be reliably measured from early adolescence, autobiographical reasoning was positively linked to identity fusion beginning in mid-adolescence. Studies 2 and 3 investigated the relationship between a woman’s first experience of childbirth and her identity fusion with other mothers. While Study 2 examined both antenatal and postpartum first-time mothers, Study 3 examined only postpartum first-time mothers. Findings demonstrated that identity fusion was stronger for women who had experienced childbirth for the first time in their lives than for women who were still pregnant with their firstborn. The pathway to identity fusion among first-time mothers manifested in different ways, such that the nature of first-time mothers’ childbirth experiences created powerful social bonds with other mothers who had also endured similar experiences. Thought processes and autobiographical reasoning mediated the pathway to identity fusion in complex ways. Identity fusion showed the potential to affect women’s psychological health outcomes after childbirth. Altogether, autobiographical memories of shared life-altering experiences are the means by which autobiographical reasoning and other post-event processes give rise to identity fusion.